IZZY : a biography of i. f. stone. - COTTRELL, ROBERT C. ([Place of publication not identified] RUTGERS University Press, 2020)
This is the classic story of the life and times of I. F. "Izzy" Stone. Robert Cottrell weaves together material from interviews, letters, archival materials, and government documents, and Stone's own writings to tell the tale of one of the most significant journalists, intellectuals, and political mavericks of the twentieth century. The story of I. F. Stone is the tale of the American left over the course of his lifetime, of liberal and radical ideals which carried such weight throughout the twentieth century, and of journalism of the politically committed variety. Now available in a handsome new Rutgers University Press Classic edition, it is an examination of the life and career of a gregarious yet frequently grumpy loner who became his nation's foremost radical commentator provides a window through which to examine American radicalism, left-wing journalism, and the evolution of key strands of Western intellectual thought in the twentieth century.
Frontmatter -- Contents -- Foreword -- Preface -- Introduction -- 1. Izzy, the Icon -- 2. Early Progress and Greater Philadelphia -- 3. On the Record -- 4. A New Deal and the Popular Front at the Post -- 5. The American Left, Interventionism, and Civil Liberties -- 6. Fighting the Good War -- 7. Going Underground -- 8. The Demise of the Old Left -- 9. The Panic Was On -- 10. A "Little Flea-Bite Publication" -- 11. "We Have to Learn to Think in a New Way" -- 12. Knockin' on Jim Crow's Door -- 13. "The Steve Canyon Comic Strip Mentality" -- 14. Telling Truth to Power: The Emperor Has No Clothes -- 15. From Pariah to Character to National Institution -- 16. An Old Firehorse in Semiretirement -- 17. A Return to the Classics -- 18. The Rock of Stone -- Acknowledgments -- Notes -- Selected Bibliography -- Index -- About the Author
eBooks on EBSCOhost
Keywords: Stone, I. F. -- 1907-1989.; Stone, I. F. -- 1907-1989; Journalists -- United States -- Biography; Journalistes -- États-Unis -- Biographies; BIOGRAPHY & AUTOBIOGRAPHY / General; Journalists; United States; I F Stone, izzy stone, journalist, intellectual, political maverick, twentieth century, liberal, radical ideals, radical commentator, American radicalism, left-wing journalism, Western intellectual, interventionism, civil liberties; Biographies